2015
DOI: 10.1111/sms.12539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcutaneous electrical nerve stimulation on quadriceps function in individuals with experimental knee pain

Abstract: Knee joint pain (KJP) is a cardinal symptom in knee pathologies, and quadriceps inhibition is commonly observed among KJP patients. Previously, KJP independently reduced quadriceps strength and activation. However, it remains unknown how disinhibitory transcutaneous electrical nerve stimulation (TENS) will affect inhibited quadriceps motor function. This study aimed at examining changes in quadriceps maximum voluntary contraction (MVC) and central activation ratio (CAR) before and after sensory TENS following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 45 publications
1
23
0
2
Order By: Relevance
“…For the control group, our findings are also consistent with previous literature indicating that the negative effects of exercise‐induced injury are short term . However, our results do not support the theory that TENS restores function via analgesic mechanisms and diverge from previous studies suggesting excitatory effects of TENS on motor output …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For the control group, our findings are also consistent with previous literature indicating that the negative effects of exercise‐induced injury are short term . However, our results do not support the theory that TENS restores function via analgesic mechanisms and diverge from previous studies suggesting excitatory effects of TENS on motor output …”
Section: Discussionsupporting
confidence: 59%
“…32,33 However, our results do not support the theory that TENS restores function via analgesic mechanisms 3 and diverge from previous studies suggesting excitatory effects of TENS on motor output. 22,73 We propose that a sensorimotor interaction following an acute episode of pain may have caused the prolonged inhibition of strength for the TENS treatment group. This is based on prior research suggesting that gross stimulation of afferent inputs may lead to changes at cortical sites and subsequently modulate motor output.…”
Section: Discussionmentioning
confidence: 93%
“…It is further worth noting that generally, pain reduces muscle strength . However, studies showed strong correlations between muscle force and either muscle volume or cross‐sectional area (CSA) .…”
mentioning
confidence: 99%
“…[22] Therefore, several studies have recommended TENS to be a safe and viable nonpharmacological analgesic resource for episiotomy pain relief[2223] as well as other pains. [242526]…”
Section: Discussionmentioning
confidence: 99%